O novo Ensino Médio: entre as normativas/orientações para a reestruturação curricular e a prática didático-pedagógica de professores da formação geral básica - Hendges, Leonardo Avelhaneda (2022)
This research was prepared based on studies carried out within the scope of the Group of Studies, Research and Interventions, Educational Innovation, Educational Practices and Teacher Training (INOVAEDUC), and is linked to the Umbrella Project “Needs for Teaching Work in Public Schools for the Effective Permanence and Qualified Learning of High School Students in Brazil (NETRADOCEM)”. The stage of Secondary Education in Brazilian Basic Education is the target of constant changes and reforms, in particular one that has recently been filling the spaces of debates about education in Brazil, namely: the curriculum reform of Secondary Education, better known as the New Teaching Medium, made public for everyone's knowledge through Provisional Measure No. 746 of September 22, 2016 and later converted into Law No. 13,415 of February 16, 2017. Among the factors that contributed to the definition of the research focus “ The didactic-pedagogical practice of General Basic Education teachers in the context of the implementation of the New High School” is the understanding that the reform process can generate multiple understandings in school contexts, in addition to problems related to its implementation. In this way, we deem it necessary that this process be analyzed with a focus, mainly, on the teaching practice and on the adaptations made in the didactic-pedagogical organization of the General Basic Formation (FGB) teachers of Secondary Education amidst the “competition” between the new curricular components and the “traditional” FGB components. Accordingly, the objective of “Establishing relations between regulations/legal guidelines regarding the New High School and the didactic-pedagogical practices developed by General Basic Education teachers in schools belonging to the 17th Regional Education Coordination” was proposed. Information was collected and analyzed through interviews with teachers working in the New High School of schools in the State Public School Network of Rio Grande do Sul (REPE/RS), belonging to the 17th Regional Education Coordination. The State School of Basic Education Professor Francisco José Damke in the city of São Paulo das Missões, RS, was defined as the research site. For the treatment and analysis of the collected information, the methodological contributions of the Grounded Theory (GT) were used, translated by the INOVAEDUC group as Theorization Rooted in Information (TEI).